1999
DOI: 10.1002/(sici)1097-4555(199906)30:6<485::aid-jrs403>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure Raman study of the perovskite BaCeO3

Abstract: A high-pressure Raman study of BaCeO 3 was performed at room temperature. This perovskite compound undergoes two phase transitions at about 22 and 28 GPa. The increase in the number of bands is an indication that the symmetry is lowered and that the compound does not evolve towards the ideal cubic perovskite structure as has been observed for some perovskites. Raman-active modes exhibit large differences in their temperature and pressure dependences, and it is impossible to deduce thermoelastic coefficients di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 16 publications
2
43
0
Order By: Relevance
“…The appearance of a Raman spectrum within the cubic symmetry with the Pm 3 m space group is quite common for the perovskite materials 15–24. For example, such a phenomenon was observed in our previous studies in the case of BaZrO 3 : Ln15, 20; the observed Raman spectrum was assumed to have its origin in the nanodomains with a symmetry different from cubic.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…The appearance of a Raman spectrum within the cubic symmetry with the Pm 3 m space group is quite common for the perovskite materials 15–24. For example, such a phenomenon was observed in our previous studies in the case of BaZrO 3 : Ln15, 20; the observed Raman spectrum was assumed to have its origin in the nanodomains with a symmetry different from cubic.…”
Section: Discussionmentioning
confidence: 61%
“…High‐pressure Raman studies of some different perovskites have already been performed. Loridant and Lucazeau16 showed the orthorhombic symmetry ( Pnma ) at low pressure values for BaCeO 3 and revealed the presence of two pressure‐induced phase transitions at 22 and 28 GPa. Chemarin et al 17 and Lucazeau18 carried out the study of BaZrO 3 and BaZrO 3 BaCeO 3 solid solutions till about 35 GPa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a wider pressure range, 0-12 GPa, but two different pressure-transmitting media, Loridant et al determined the bulk modulus of SrCeO 3 to be 127(3) GPa with a pressure derivative of 4.2(8) [20]. The bulk modulus for SrCeO 3 determined by neutron diffraction, lies between the two values for BaCeO 3 that were derived from Raman data by Loridant and Lucazeau [32] (91 GPa for ∼0 GPa≤ P ≤ 5 GPa, and 125 GPa for 5 GPa≤ P ≤ 10 GPa). The measured bulk moduli for the cerate perovskites are significantly smaller than those measured for other A II B IV O 3 [34], CaSnO 3 (167 GPa) [35], CdTiO 3 (214 GPa) and CdSnO 3 (185 GPa) [36].…”
Section: Resultsmentioning
confidence: 94%
“…Figure 5 reproduced from Ref. 25 gives an answer to this question. One can verify that plots of the wavenumber variations versus relative volume cell variations of the perovskite BaCeO 3 do not coincide for the phonon at about 350 cm 1 while high-pressure plots and low-temperature plots are in good coincidence for the phonon at about 340 cm 1 .…”
Section: Isotropic Approximationmentioning
confidence: 97%